Pengaruh Sales Growth, Debt To Equity Ratio, Total Assets Turnover Terhadap Return On Assets Pada Perusahaan Property Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia 2018-2020 - Dian Ramli; Yusnaini Yusnaini (Politeknik Ganesha Medan, 2022)
The purpose of this study was to determine the effect of Sales Growth, Debt to Equity Ratio, Total Assets Turnover to Return on Assets property and real estate sector companies that listed in Indonesia Stock Exchange. The population in this study are supporting property and real estate sub-sector companies listed on Indonesia Stock Exchange from 2018-2020. By using a sampling technique (purposive sampling) gained 49 (forty-nine) companies that will serve as the object of research. The testing method used to see the effect of indenpent variables on the dependent variabel is the data panel regression analyze method. Based on this research stimultaneously the effectiveness of Sales Growth not significantly to Return on Asset but Debt to Equity Ratio, Total Assets Turnover on Return on Assets significantly influence Return on Assets. Partial test shows that the effectiveness of Sales Growth has a positive effect but not significant Return on Assets. Debt to Equity Ratio has a negative and significant on Return on Assets. Total Assets Turnover has a positive and significant.